Oil Well Health Monitoring and Intelligent Controlling Using Wireless Sensor Network - Sharmila. R; Suganya. A; Gnanavel. G (International Journal of Computer Sciences and Engineering, 2014)
Most oil pumping units (OPUs) have been using manual control in the oilfield. This existing oil- pumping system has a high power-consuming process and has incapabilityï¿½s of OPUï¿½s structural health monitoring. Due to the environmental conditions and remote locations of oil sites, it is expensive to physically visit for maintenance and repair. This paper develops a sensor network based intelligent control is proposed for power economy and efficient oil well health monitoring. The system consists of several basic sensors such as voltage sensor, level sensor, MEMS sensor, temperature sensor and gas sensor. The sensed data is given to the ARM controller which processes the oil wells data and it is given to the oil pump control unit which controls the process accordingly. If any abnormality is detected then the fault is informed to the maintenance manager. The malfunction is sent as an SMS to the managerï¿½s mobile via GSM.